Nas tintas da história : a produção de pinturas históricas de temática farroupilha na república velha gaúcha - Nascimento, Marlene Ourique do (2019)
The present thesis aims at the analysis of a set of historical paintings about the Farroupilha Revolution produced by the government of the state of Rio Grande do Sul between the end of the 19th century and the beginning of the 20th century. From the organization of those Works production documents and on the assumptions of Cultural History this study aims to elucidate the hypothesis of appropriation of the republican character of the revolution by the Rio Grande Republican Party in the context of the old gaucho republic. In this sense, the constitutive elements of this scenario were organized as means of the production processes of the paintings taken as subject of this study, such as the construction of the Piratini Palace, the creation and performance of the Júlio de Castilhos Museum, the elaboration of cultural management in the state of Rio Grande do Sul, as well as the constitution of the Southern Brazilian artistic environment on the turn of these centuries. From these data it is possible to point to the PRR actions inserted in the context of the historiographic debate about the Farroupilha, as a determinant fact for the production and for the route traced by these objects.